Numerical investigation of vortex tubes with extended vortex chambers - Matveev, Konstantin I.; Leachman, Jacob (International journal of refrigeration, 2019)
Ranque–Hilsch vortex tubes are often utilized to produce cooling when a compressed air source is readily available. In comparison with traditional cooling technologies, vortex-tube devices are much simpler, since they do not have moving parts. However, their thermal efficiencies are also lower, so they are used primarily for industrial spot cooling. Several options to modify and improve vortex tube performance exist. While a lot of previous research efforts addressed optimization of the inlet and outlet components, the main tube variations have not been thoroughly explored beyond simple tapered tubes. In this paper we numerically investigate augmenting vortex tubes with cyclonic-type extensions of the vortex chambers. The computational fluid dynamics software STAR-CCM+ was utilized to simulate a typical counter-flow vortex tube operating with air. The numerical approach was validated via comparison to experimental studies available in the literature. A reasonably efficient high-capacity vortex tube design was parametrically analyzed. This setup and its several modifications were numerically modeled under selected external conditions. The configuration with an intermediate-size vortex chamber extension demonstrated the highest performance among the studied setups. This variant of the vortex tube was also predicted to perform better than the original system by about 15% in a range of cold-flow fractions.